Implementation Of Learning The Safinatun Najah Book Towards Improving Women's Understanding Of Fiqh At The Al-Intiqol Islamic Boarding School In Cianjur - Abdul Basir; Asep Supriyadi; Mifta Hussa'adah (Pasundan Social Science Development, 2026)
This study aims to investigate the implementation of learning the Safinatun Najah book in improving female students' understanding of women's fiqh at Al Intiqol Islamic Boarding School, Cianjur. Using a qualitative approach and case study design, this research involved 10 female students as participants. Data were collected through participatory observation, in-depth interviews, questionnaires, cognitive tests, and documentation. The learning process was carried out using the bandongan method during general lectures and the sorogan method during supervised group study sessions. The materials focus on women's fiqh, especially menstruation (menstruation), postpartum bleeding (nifas), irregular bleeding (istihadhah), and purification (thaharah). The results indicate that the Safinatun Najah learning method has a positive impact on students' comprehension, as demonstrated by significant improvement in their ability to distinguish between types of blood and understand purification laws. This improvement was supported by cognitive test results where 8 out of 10 participants scored above 80, and interviews confirmed a better understanding of fiqh principles. In conclusion, the implementation of Safinatun Najah plays an essential role in shaping female students' understanding of women's fiqh in the Islamic boarding school environment.